Variation in opioid prescribing patterns after abdominal transplant surgery. Issue 10 (9th August 2021) - Sussman, Jon; Calderon, Esteban; Ubl, Daniel S.; Croome, Kristopher P.; Taner, C. Burcin; Heimbach, Julie K.; Moss, Adyr; Habermann, Elizabeth B.; Mathur, Amit K.
Abstract: Background: Opioids are associated with negative transplant outcomes. We sought to identify patient and center effects on over‐prescribing of opioids (> 200 OME (oral morphine equivalents)). Study design: Clinical and opioid prescription data (2014–2017) were collected from three academic transplant centers for kidney (KT), liver (LT), and simultaneous liver‐kidney transplant (SLK) patients. Multivariable models were used to identify predictors of opioid over‐prescribing at discharge and the occurrence of refill prescriptions at 90 days. Results: Three‐thousand seven‐hundred and two patients underwent transplant in the cohort (KT: n  = 2358, LT: n  = 1221, SLK: n  = 123). More than 80% of recipients were over‐prescribed opioids at discharge (Median OME (mOME) = 300 (IQR 225–375). LT and SLK had the largest prescription size (LT mOME 338 (IQR 300–450); SLK mOME 338 (IQR 225–450) and refill rate (LT: 64%, SLK 59%) (all, P  < .001). Multivariable analysis indicated that transplant center was a significant predictor of opioid over‐prescription after KT and LT (all, P  < .001); older age (in KT) and length of stay (LOS) (in LT) were protective factors (both, P  < .05). Refill occurrence was associated with initial prescription size and was reduced by older age and initial LOS (all, P  < .05). Conclusions: The wide variation in opioid prescribing patterns has implications for transplant practice innovation, guideline development, and further study.